The long-term movement of the terms of trade between agricultural and industrial products - Atallah, Muhammad Karam. [from old catalog] (Delft, 1958)
The book is a systematic study of the main factors which determine the terms of trade between agricultural and industrial countries in the long run.
gau 27/02/17
loans
Keywords: Commerce